5(p)+2(1-p)=4(p)+7(1-p)

Simple and best practice solution for 5(p)+2(1-p)=4(p)+7(1-p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(p)+2(1-p)=4(p)+7(1-p) equation:


Simplifying
5(p) + 2(1 + -1p) = 4(p) + 7(1 + -1p)
5p + (1 * 2 + -1p * 2) = 4(p) + 7(1 + -1p)
5p + (2 + -2p) = 4(p) + 7(1 + -1p)

Reorder the terms:
2 + 5p + -2p = 4(p) + 7(1 + -1p)

Combine like terms: 5p + -2p = 3p
2 + 3p = 4(p) + 7(1 + -1p)
2 + 3p = 4p + (1 * 7 + -1p * 7)
2 + 3p = 4p + (7 + -7p)

Reorder the terms:
2 + 3p = 7 + 4p + -7p

Combine like terms: 4p + -7p = -3p
2 + 3p = 7 + -3p

Solving
2 + 3p = 7 + -3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '3p' to each side of the equation.
2 + 3p + 3p = 7 + -3p + 3p

Combine like terms: 3p + 3p = 6p
2 + 6p = 7 + -3p + 3p

Combine like terms: -3p + 3p = 0
2 + 6p = 7 + 0
2 + 6p = 7

Add '-2' to each side of the equation.
2 + -2 + 6p = 7 + -2

Combine like terms: 2 + -2 = 0
0 + 6p = 7 + -2
6p = 7 + -2

Combine like terms: 7 + -2 = 5
6p = 5

Divide each side by '6'.
p = 0.8333333333

Simplifying
p = 0.8333333333

See similar equations:

| -3(y+9)=36 | | -9a^6c^4(5c^3+3a-6)= | | v/9=11/5 | | 2b^2-13b+6=0 | | -4y-y-6=14 | | -7x-2=-30 | | 7/3=9/u | | 0.20x+0.45(50)=33.5 | | A(r)=4(3.14)r^2 | | 4p+3(1-p)=p+7(1-p) | | 25=9+(9x+2) | | -d+46=26 | | 1x+9= | | x^2+4x+y^2+6y+63=0 | | -4+46=26 | | 110=-10-8x | | 9x+4y=65 | | 2(4k-3)=3k-38 | | m/5 | | 6b-3=5a+1 | | -4p+(-1)(1-p)=1p+(-2)(1-p) | | 118/13=u/6 | | 3/5=y/7 | | 45x+32m=6 | | 2a+6=3a-10 | | 4w-21+7w=45 | | (7y+6)-(4+6y)=8 | | -6y+12+2y=40 | | Xsquared+10x+6=0 | | -5x=1+x-4-3x | | (3c-4t)(3c+3t)= | | 7/y=11/17 |

Equations solver categories